Islam Masa Periode Spanyol - Mardhiyya, Alkhonsa; Mawardi, Kholid (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
After the death of Prophet Muhammad SAW. Islam needs a replacement for him to lead the Muslims. While the Prophet Muhammad SAW did not leave a will regarding who would replacehim after he died. Islamic leaders at that time knew very well that Islam needed a leader, namely a caliph who wes chosen through deliberation. Finally, the Prophet’s companions were elected ascaliphs in the order of Abu Bakr Ash-Shidiq, Umar bin Khattab, Uthman bin Affan and Ali bin Abi Thalib. The determination of the Ottoman manuscripts to exist during the time of Uthman bin Affan and the existence of total unity that exist in the text of the Koran throughout the world with varios sects in the world is one from of the success of the caliph Uthman bin Affan which cannot be rivalled by anyone in uniting Muslims. Political problems during the time of Ali bin Abi Talib eventually brought Islam to the strunggle for theology or theology which led to the emergence of three schools of thought.Key Words: Head of State, Caliph Period, Ottoman Manuscripts.